Video Blog Advertising: Feedback Analysis - V. Gundarin, M; A.I. Zotova, A; Y. Ilina, I; E. Nakhratova, E; V. Makarova, I (International Journal of Engineering and Technology, 2018)
In recent years, a new market trading in cryptocurrencies and instruments based on them has been formed. The market of this paper The Internet, as a result of the gradual development of information technologies, has become an advanced communicative means resulting in totally new communication forms. At this stage of development, Internet technologies promote social growing-up of a person in communities. At this point in the history of the Internet, we face the problem of studying the social aspect of virtual reality. Participants in social and political processes have shown their interest in investigating the Internet phenomenon, including its role in different spheres of public life, since the moment of its formation. Such communicative means as video blogs are of key importance. The urgency of this issue is multifaceted. Thus, the article presents results of the content analysis of the target audience feedback referred to video blog advertising. The findings enable to optimize advertisersâ€™ use of such channel of promotion as video blogs.Â Â